Basic concepts for crew resource management and non-technical skills. Issue 1 (March 2015) - Flin, Rhona; Maran, Nikki
Abstract : In this paper, we explain the conceptual background to non-technical skills and show how they can influence job performance in anaesthesia. We then describe the taxonomy of anaesthetists' non-technical skills (ANTS) and related systems, such as ANTS-AP for anaesthetic practitioners. We discuss the training courses that have been designed to teach these non-technical skills, which are called crew resource management (CRM), crisis resource management (CRM) or crisis avoidance resource management (CARMA). Finally, we discuss the application of non-technical skills assessment systems.